Mit livs OL-eventyr - det personlige møde med De Olympiske Lege - Wøllekær, Johnny (Forum for Idræt, 2003)
Danske OL-deltageres møde med de olympiske lege. Bl.a. svømmeren Jytte Hansen i 1948. My life’s Olympic fairytale – a personal encounter with the Olympic games Odense City Archives has a project running at the moment in which erstwhile participants in the Olympics Games tell their Olympic stories. With the help of a range of volunteers, the archive has had interviews conducted and collected material from and about earlier Olympic participants from Odense. It is the participants’ own personal experiences and their encounter with the Olympic Games which lies at the heart of this little survey, one of whose functions is to provide documentation for the colossal changes which élite sport has undergone during the past 100 years. When we read and listen to the participants’ encounter with the Olympic Games, we quickly sense the huge and decisive significance they had on people’s lives. This is not to say that the Olympics changed everything, for everyday life returned again. Many, however, took home with them positive memories and experiences, even though they never got anywhere near winning a medal. When the Danish participants with the Danish flag at their head marched in to the Olympic stadium and felt the roar of the multitude of spectators, many of them felt a lump in their throat. Expressions like ”an unbelievable experience” or ”my life’s fairytale” recur frequently in the interviews. A chronological reading of the many interviews does not only tell the story of each sportsperson’s experiences. Taken as a whole, they also reflect the way in which Danish élite sport gradually became better organized, became more professional. While sporting talents in the 1940s and 50s were more or less left to themselves during the preparations for the games – and even during the games themselves – in the 1960s and 70s training camps, special trainers and the like began to emerge. (20) Participants were selected earlier so there was plenty of time for optimal preparation, just as it became easier to take time off to prepare for the Olympic Games.